The Effects of Digital Word-Of-Mouth on Brand Image and Purchase Intention - Fatima SAYAH (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2022)
This study investigates the impact of electronic word-of-mouth (e-WOM) on consumer behaviour, and more specifically on product brand image and purchase intention. After a brief review of the academic literature, The research employs a survey-based method. The structured questionnaire was designed using google forms and was shared online. Using a 20 question and convenience sampling method, the data were collected from 140 consumers in Algeria. The results of the data analysis, using PLS. V3 structural equations, show that e-WOM has a positive and significant impact on brand image and purchase intention, and that the WOM and BI have a significant positive impact on PI.